Hybrid inorganic-organic nano- and microcomposites based on silica sols and synthetic polyelectrolytes (eXPRESS Polymer Letters)
Interaction between anionic (and cationic) colloidal particles of silica having the particles diameters 12 and 22 nm with synthetic cationic (and anionic) polyelectrolytes of various nature and structure was studied by potentiometric, conductimetric spectroturbidimetric and viscometric methods in aqueous solution. It was shown that the complexation of silica nanoparticles with linear polyelectrolytes leads to formation of mostly stoichiometric interpolyelectrolyte complexes (IPEC) which precipitate from aqueous solution. Casting of water-soluble IPEC followed by thermal treatment gives thin composite films insoluble in water while ‘layer by layer’ (LbL) deposition of polyelectrolyte components onto silica sols leads to formation of multilayered nano- and microcomposites. The possible mechanism of formation of LbL multilayers consisting of silica sol (SiO2) ‘cores’ and polyethyeleneimine-polyacrylic acid (PEI-PAA) ‘shells’ was suggested. It was found that in diluted aqueous solution the radius of gyration, Rg and hydrodynamic radius, Rhmean of LbL particles are independent on LbL concentration and smaller than 100 nm. The zeta potential values of LbL particles are arranged between –10 and –30 mV. The average size of LbL particles estimated by scanning electron microscopy (SEM) is in the range of 200–500 nm. Thermal treatment of LbL multilayers followed by etching of (SiO2) ‘core’ by HF leads to formation of a series of spherical nanocavities and blob-like microcavities.